Metode Asessment Center sebagai sarana pengembangan Sumber Daya Manusia melalui identifikasi potensi dan kompetensi SDM - Wustari L. Mangundjaya (Journal on Education, 2024)
To strive and expand organizations need to have competent and loyal employees who can be dependable enough not only for the present condition but also to be the future leaders of the organizations. This condition makes organizations need to conduct employee identification of their potential and competency. The results of the identification to be used not only for putting the employees based on the right man and the right place but also to identify potential employees that can become the talent. There are many methods can be used for this program and one of it is using the method of Assessment Center. By using this method with many varieties of the assessment the results of the employee assessment will be more complete. This paper will discuss about the implementation of the Assessment Center method to identify the potential and competent employees to become the talent and the future leader of the organization.